Behavioural interventions for sleep: who prefers what? - Hemmings, Nicholas (My University, 2017)
Many university students have trouble sleeping because their minds are too active with worries and other sleep disruptive thoughts they are unable to control. Previous research has compared two self-help intervention: Structured Problem-solving, which involves scheduling time earlier in the day to write out worries and steps toward solutions; and Beaudoin’s Somnotest APP, which uses mental imagery to prevent sleep disruptive thoughts. Both interventions were equally effective alone or in combination. Nevertheless, there were individual differences in how students responded to the interventions. Our study extends previous research by examining these individual differences. We examined students’ preferences for interventions in relation to their circadian preference (morning types and evening types) and their preferred way of coping with stress (i.e, emotion focused vs. problem focused). We predict that students who prefer problem-focused coping will also prefer Structured Problem-solving, whereas those who prefer emotion-focused coping will favour the APP. Since evening types take longer to fall asleep, we predict that they may find the APP less effective because it could be arousing. Participants consisted of 131 MacEwan University students who were poor sleepers. They completed standardized measures of sleep and arousal (Sleep Quality Scale, Glasgow Sleep Effort Scale and Pre-Sleep Arousal Scale), ways of coping with stress (COPE) and circadian preference ( Composite Scale of Morningness). Data analysis will be completed by April. Results and implications will be discussed.
Presented on April 24, 2017 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: sleep; students